2020
DOI: 10.1002/cac2.12017
|View full text |Cite
|
Sign up to set email alerts
|

Association of chromosome 7 aneuploidy measured by fluorescence in situ hybridization assay with muscular invasion in bladder cancer

Abstract: Background: The preoperative prediction of muscular invasion status is important for adequately treating bladder cancer (BC) but nevertheless, there are some existing dilemmas in the current preoperative diagnostic accuracy of BC with muscular invasion. Here, we investigated the potential association between the fluorescence in situ hybridization (FISH) assay and muscular invasion among patients with BC.A cytogenetic-clinical nomogram for the individualized preoperative differentiation of muscle-invasive BC (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Blood indicators, including lactate dehydrogenase (LDH) (18), the NLR (neutrophil-to-lymphocyte ratio) (19), the PLR (platelet-to-lymphocyte ratio) (20), the LMR (lymphocyteto-monocyte ratio) (21), carbohydrate antigen 125 (CA125) (22), and carbohydrate antigen 153 (CA153) (23), have shown important diagnostic and/or prognostic value in ovarian cancer. Additionally, nomograms, considered as a clinically easy-to-implement and reliable calculating model, have been established by combining related risk factors to help clinicians to develop individualized treatment and follow-up management strategies in breast, gastric and bladder cancers (24)(25)(26)(27). These have attracted our attention to devise such a model for HGSOC.…”
Section: Introductionmentioning
confidence: 99%
“…Blood indicators, including lactate dehydrogenase (LDH) (18), the NLR (neutrophil-to-lymphocyte ratio) (19), the PLR (platelet-to-lymphocyte ratio) (20), the LMR (lymphocyteto-monocyte ratio) (21), carbohydrate antigen 125 (CA125) (22), and carbohydrate antigen 153 (CA153) (23), have shown important diagnostic and/or prognostic value in ovarian cancer. Additionally, nomograms, considered as a clinically easy-to-implement and reliable calculating model, have been established by combining related risk factors to help clinicians to develop individualized treatment and follow-up management strategies in breast, gastric and bladder cancers (24)(25)(26)(27). These have attracted our attention to devise such a model for HGSOC.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the tumor size in BCa staging has been evaluated in several studies, which revealed that the tumor size in MIBC was larger than that in non‐muscle‐invasive BCa 13,15,16 . In this study, the tumor's largest size over 3 cm was an independent risk factor for MIBC with stalk.…”
Section: Discussionmentioning
confidence: 59%
“…), which may lead to tumor recurrence or a poor prognosis. 32 The histological grade of BLAC represents the degree of tumor differentiation and is usually used to evaluate the prognosis of tumor treatment. 33 High-grade BLCA represents a higher risk of recurrence, metastasis, and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…If MIBC patients are undertreated or their treatment is delayed due to understaging as NMIBC, they will not receive optimal treatment (such as neoadjuvant chemotherapy, RC, etc. ), which may lead to tumor recurrence or a poor prognosis 32 . The histological grade of BLAC represents the degree of tumor differentiation and is usually used to evaluate the prognosis of tumor treatment 33 .…”
Section: Discussionmentioning
confidence: 99%